Association between physical activity and episodic memory and the moderating effects of the apolipoprotein E ε4 allele and age - Lee, Boung Chul; Choe, Young Min; Suh, Guk-Hee; Choi, Ihn-Geun; Kim, Hyun Soo; Hwang, Jaeuk; Yi, Dahyun; Kim, Jee Wook (Frontiers in Aging Neuroscience, 2023)
Background An abundance of evidence indicates that physical activity may protect against Alzheimer’s disease (AD) and related cognitive decline. However, little is known about the association between physical activity and AD-related cognitive decline according to age and the apolipoprotein E (APOE) ε4 allele (APOE4) as major risk factors. Therefore, we examined whether age and APOE4 status modulate the effects of physical activity on episodic memory as AD-related cognition in non-demented older adults. Methods We enrolled 196 adults aged between 65 and 90 years, with no dementia. All participants underwent comprehensive clinical assessments including physical activity evaluation and APOE genotyping. The AD-related cognitive domain was assessed by the episodic memory, as the earliest cognitive change in AD, and non-memory cognition for comparative purposes. Overall cognition was assessed by the total score (TS) of the Consortium to Establish a Registry for Alzheimer’s Disease neuropsychological battery. Results We found significant physical activity × age and physical activity × APOE4 interaction effects on episodic memory. Subgroup analyses indicated that an association between physical activity and increased episodic memory was apparent only in subjects aged > 70 years, and in APOE4-positive subjects. Conclusion Our findings suggest that physical activity has beneficial effects on episodic memory, as an AD-related cognitive domain, in individuals aged > 70 years and in APOE4-positive individuals. Physicians should take age and APOE4 status account into when recommending physical activity to prevent AD-related cognitive decline.